Use of Mathematics in Deuda Naach: Logic and Geometry (Spandan, 2018)
The major concern of this article is to explore the use of mathematics on Deuda Dance in Karnali State and it can be use in teaching learning process in mathematics class. Specifically, Deuda Dance is improve students’ math skills, critical thinking, logical skills and creativity, as well as enhance student motivation, socio-emotional and motor skills. The pleasant nature of the activities is also highlighted, an element that is believed to make this method adequate for students of low achievement in math. Deuda players make different geometrical shapes according to the different rhythm of Deuda songs. The body movement and the steps of the foots of kheladi (players/dancer) are more interesting and meaningful for geometry teaching, on the other hand, singing songs at the time of Deuda dance also interesting and mathematical logics are used in songs.